2010
DOI: 10.1002/iroh.201011205
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton Density Prediction in a Flood Lake (Pantanal – Brazil) Using Artificial Neural Networks

Abstract: Ecologic relationships are usually non-linear and highly complex. For this reason, artificial neural networks (ANN) were selected to model zooplankton density groups in the Coqueiro lake in the northern Pantanal of Brazil. The input layer used 11 limnological variables with 13 neurons in the hidden layer; the output layer consisted of three zooplankton groups. Samples were collected monthly between April 2002 and May 2003, at three different points of the lake, two of which were used for training the ANNs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
2
2
0
1
Order By: Relevance
“…The EE values in the other compartments were high, demonstrating the importance of all of these groups as prey and/or predators. The estimated values of the zooplankton biomass (between 2.24 and 3.62) are comparable to those that were observed in the Pantanal floodplain by Fantin-Cruz et al (2010).…”
Section: Output Modelssupporting
confidence: 86%
“…The EE values in the other compartments were high, demonstrating the importance of all of these groups as prey and/or predators. The estimated values of the zooplankton biomass (between 2.24 and 3.62) are comparable to those that were observed in the Pantanal floodplain by Fantin-Cruz et al (2010).…”
Section: Output Modelssupporting
confidence: 86%
“…This situation is to be expected in the majority of shallow environments with a developed littoral zone colonized by macrophytes (Fantin-Cruz et al, 2010;Sousa & Elmoor-Loureiro, 2012). Rotifer species registered in this study belonged to Lecanidae, family inhabiting shallow and littoral areas and often associated with plants ( Padovesi-Fonseca et al, 2011;Siddiqi & Karuthapandi, 2013).…”
Section: Factors That Structure the Beta Diversity Of Zooplankton Comsupporting
confidence: 54%
“…fish and macroinvertebrates) and play a key role in cycling of organic materials in an aquatic ecosystem (Kozlowsky-Suzuki & Bozelli, 2002;Matsumura-Tundisi & Tundisi, 2005;Norlin et al, 2006). Studies has been performed in different time intervals, as the interannual (Lansac-Tôha et al, 2009), monthly (Ortega-Mayagoitia et al, 2000Fantin-Cruz et al, 2010), and/or weekly variation cycle (Chittapun et al, 2009), derived from the different sampling frequencies of the zooplankton in various types of wetlands (Bottrell et al, 1976;Guseska et al, 2012). The zooplankton species also positivamente com macrófitas aquáticas (devido ao aumento de nichos e refúgio), enquanto que lagos com maior proximidade geográfica aumentou a similaridade na composição das espécies, e diminuindo a diversidade de β. Conclusões: Os processos determinísticos (teoria do nicho), por haver muitas espécies com diferentes requisitos ecológicos, apresentaram respostas diferentes aos gradientes ambientais e foram responsáveis por aumento da diversidade em sistemas lêntico mais heterogênios.…”
Section: Introductionunclassified
“…Studies carried out on the Paraná (Bonecker et al, 2005;Lansac-Tôha et al, 2009;Dias et al, 2014), Pantanal (Fantin-Cruz et al, 2010), and Amazon (Carvalho, 1983;Bozelli, 1994;Hardy et al, 1994) floodplain have shown that the structure of the zooplankton community changes with variations in physical and chemical attributes of water during the high-water period. Floodplains are characterised by high environmental heterogeneity, including lotic, semilotic, and lentic environments.…”
Section: Introductionmentioning
confidence: 99%